Strength of soft clay embedded with single crushed polypropylene (PP) column - Lee, Jie Yen (2016)
Stone column could be used as a ground improvement technique where a portion of soft soil is replaced with granular material such as stone or sand. The benefit of using stone columns in low strength soil has been proved as an efficient method to improve bearing capacity and reduce settlement of soft soils. This study was aimed to investigate the improvement in shear strength of soft clay by embedded with a group of pellet polypropylene column (PP column). This paper was done by determine the effect of area replacement ratio and height penetration ratio of a single PP column on shear strength characteristics. Unconfined Compression Triaxial Test (UCS) was conducted for 7 batch kaolin samples including control sample in order to determine the shear strength. The research variable are diameter and height of polypropylene column which under a concept of critical length of column. The increment of shear strength by embedded with PP column are 58.23%, 47.50% and 48.93% with 10.24% area replacement ratio at column penetration ratio of 0.30, 0.50 and 0.80 respectively. Meanwhile, having 25% area replacement ratio, the improvement of shear strength are 91.24%, 42.78% and 25.30% at column penetration ratio of 0.30, 0.50 and 0.80 respectively. From the result obtained, the relationship of the increment of shear strength with the various column penetration show different pattern.